AplikasiBerbagaiPupukPelengkap CairDenganBeberapa Interval PenyemprotanTerhadap Pada TanamanKedelai (Glycine max (L) Merril) - Kriswanto, Leo; Rasyad, Aslim; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study was intended to determine the effect of foliar supplemented fertilizer (FSF) applied at different spraying intervals on vegetative growth and yield components of soybean.The study was conducted in Faculty of Agriculture Experiment station from March to June 2018 using a split plot design with three replications. Three levels of spraying intervals such as,W1= every 5 days, W2= every 8 days, W3= every 11 were assigned as main plot and three levels of FSF P1= Gandasil D, P2= Bayfolan, and P3= Growmore were assingned as sub plots. Traits observed were plant height, flowering date, harvesting time, total number of pods, number of filled pods per plant, number of seeds per plant, weight of seeds per plant, yield per m2, and 100-seed weight. Data were analyzed by the method of analysis of variance and followed by the least significant difference at p= 0.05. Where as the real interaction effect was seen the difference in time of application of liquid complementary fertilizer for each type of FSF.The results showed that the treatment of various types of FSF significantly affected the date of harvest. Spraying time intervals significantly affect flowering age, number of seeds per plant and yield per m2. The interaction of various types of FSF and spraying time intervals significantly affected plant height, total number of pods, number of pods, seed weight per plant and yield per m2.Â Keywords : foliar fertilizer, spraying interval, yield component.